First VLBI Detection of the Radio Remnant of Supernova 1987A: Evidence for Small-Scale Features - Ng, C; Potter, T; Staveley-Smith, L; Tingay, Steven; Gaensler, B; Phillips, C; Tzioumis, A; Zanardo, G (Institute of Physics Publishing Ltd., 2012)
We present a detailed analysis of the first very long baseline interferometry (VLBI) detection of the radio remnant of supernova 1987A. The VLBI data taken in 2007 and 2008 at 1.4 and 1.7 GHz, respectively, provide images sensitive to angular scales from 0farcs1 to 0farcs7, the highest resolution to date at radio frequencies. The results reveal two extended lobes with an overall morphology consistent with observations at lower resolutions. We find evidence of small-scale features in the radio shell, which possibly consist of compact clumps near the inner surface of the shell. These features have angular extent smaller than 0farcs2 and contribute less than 13% of the total remnant flux density. No central source is detected in the VLBI images. We place a 3s flux density limit of 0.3 mJy on any pulsar or pulsar wind nebula at 1.7 GHz.